Strategia promocji miasta na przykładzie Wałbrzycha = Town promotion strategy. The case of Wałbrzych - Glinka, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this article is to present the formal and legal foundations of the promotion of Wałbrzych. Therefore, it outlines the assumptions of the most important documents of strategic character which refer to promotional actions.
Keywords: Wałbrzych; promocja